A battery cell, a battery, and an electric device

CN122968588APending Publication Date: 2026-10-23CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510497959.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-21
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

电池单体中隔膜基膜为PE薄膜或者PP薄膜,二者的拉伸强度和穿刺强度都不高,不能满足电池单体的使用要求,降低了电池单体的安全可靠性

Benefits of technology

[0004]本申请是鉴于上述课题而进行的,其目的在于,提供一种电池单体、电池和用电装置,其中改善了电池隔离膜拉伸性能和穿刺性能较低的问题,从而提升了电池单体的安全可靠性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122968588A_ABST
    Figure CN122968588A_ABST
Patent Text Reader

Abstract

A battery cell, a battery and a power utilization device are provided. The battery cell comprises a separator film, the separator film comprising a base film and an organic coating layer, wherein the organic coating layer is located on at least one side surface of the base film. The organic coating layer comprises polyester silicone organic particles and biomass nanofibers, wherein the biomass nanofibers are coated on at least part of the surface of the polyester silicone organic particles. The application improves the problem that the tensile property and the puncture property of the battery separator film are low, thereby improving the safety and reliability of the battery cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of battery technology, and more specifically, to a battery cell, a battery, and an electrical device. Background Technology

[0002] With increasing environmental pollution, the new energy industry is attracting more and more attention. Within the new energy industry, battery technology is a crucial factor in its development.

[0003] The development of battery technology requires consideration of various design factors, such as energy density, cycle life, capacity, and safety and reliability. The separator base film in a battery cell is typically PE or PP film, both of which have low tensile and puncture strength, failing to meet the usage requirements of the battery cell and reducing its safety and reliability. Therefore, improving the battery separator to enhance the safety and reliability of the battery cell is a pressing technical problem that needs to be solved. Summary of the Invention

[0004] This application is made in view of the above-mentioned problems, and its purpose is to provide a battery cell, a battery and an electrical device, wherein the problem of low tensile and puncture performance of the battery separator is improved, thereby improving the safety and reliability of the battery cell.

[0005] In a first aspect, a battery cell is provided, comprising: a separator, the separator comprising a base film and an organic coating, the organic coating being located on at least one side surface of the base film, the organic coating comprising polyester siloxane organic particles and biomass nanofibers, wherein the biomass nanofibers coat at least a portion of the surface of the polyester siloxane organic particles.

[0006] In this embodiment, an organic coating is introduced on at least one side of the base membrane of the separator. The coating uses polyester-based siloxane organic particles as the main filler, which has good flexibility and thermal stability, and can improve the shrinkage resistance of the separator. At the same time, biomass nanofibers are introduced into the coating, which combine with the polyester-based siloxane organic particles and coat at least part of the surface of the polyester-based siloxane organic particles. Since the surface of the biomass nanofibers contains many oxygen-containing groups, strong hydrogen bonds can be formed between the fibers, resulting in very high strength and modulus of the biomass nanofibers. The polyester-based siloxane organic particles also have a large specific surface area, and the surface of the particles also has polar groups such as hydroxyl groups that form strong hydrogen bonds with the biomass nanofibers, providing conditions for the adhesion of biomass nanofibers. By coating the polyester-based siloxane organic particles with biomass nanofibers, the slippage between the polyester-based siloxane organic particles can be suppressed while ensuring the separator has shrinkage resistance, thereby improving the overall flexibility of the organic coating, and thus improving the tensile properties and puncture resistance of the separator, and improving the safety and reliability of the battery cell.

[0007] In some feasible implementations, the aspect ratio D of the biomass nanofibers in the organic coating satisfies the following condition: 20:3 ≤ D ≤ 100:1. If the aspect ratio of the biomass nanofibers is too large, their specific surface area will be larger, leading to agglomeration between the nanofibers. Conversely, if the aspect ratio is too small, their specific surface area will be smaller, resulting in weak inter-fiber bonding and insufficient transmission of external forces, thus failing to provide significant reinforcement. Therefore, by controlling the aspect ratio of the biomass nanofibers within the aforementioned range, the biomass nanofibers in the separator can exhibit better mechanical properties, improving the tensile and puncture resistance of the separator and enhancing the safety and reliability of the battery cells.

[0008] In some feasible implementations, the length of biomass nanofibers in the organic coating is between 100 nm and 500 nm. Excessive length prevents the biomass nanofibers from effectively coating the surface of the organic particles, while insufficient length leads to weak inter-fiber bonding, hindering the transfer of external forces and resulting in ineffective reinforcement. Therefore, controlling the length of the biomass nanofibers within this range allows for better mechanical properties in the separator, improving its tensile and puncture resistance, and ultimately enhancing the safety and reliability of the battery cells.

[0009] In some feasible embodiments, biomass nanofibers include at least one of cellulose nanofibers and chitin nanofibers. The surfaces of these biomass nanofibers contain oxygen-containing groups, and strong hydrogen bonds can form between the fibers, resulting in high strength and modulus. Using these biomass nanofibers can improve the overall tensile strength and puncture resistance of the membrane.

[0010] In some feasible implementations, polyester-based siloxane organic particles include at least one of: methylsiloxane stearate, aminopropylsiloxane-polyethylene glycol ester, and sulfonated siloxane-polyester copolymer. These polyester-based siloxane organic particles have a large specific surface area, and the polar groups on their surface allow for better adhesion of biomass nanofibers.

[0011] In some feasible implementations, the specific surface area A of polyester siloxane organic particles satisfies: 10 m² / g. 2 / g≤A≤100m 2 / g. By controlling the specific surface area of ​​the polyester siloxane organic particles within this range, biomass nanofibers can better adhere to and coat the particle surface, allowing for better bonding between the two. If the specific surface area of ​​the polyester siloxane organic particles is too large, agglomeration will occur between the particles; if the specific surface area is too small, there will be insufficient surface area for the biomass nanofibers to adhere, causing the nanofibers to remain in a free state within the coating. Therefore, controlling the specific surface area of ​​the polyester siloxane organic particles within this range can improve the tensile and puncture resistance of the separator, thereby enhancing the safety and reliability of the battery cells.

[0012] In some feasible implementations, the mass ratio E of biomass nanofibers to polyester siloxane organic particles in the organic coating of the separator satisfies: 1:99 ≤ E ≤ 1:9. The biomass nanofibers in the coating act as reinforcing fillers. If the fiber content is too high, the biomass nanofibers in the mixture of biomass nanofibers and polyester siloxane organic particles will adhere excessively and exist in an agglomerated form. Since biomass nanofibers are high-modulus and high-strength materials, their agglomerated existence will make the entire coating hard and brittle, with poor film-forming properties and a tendency to crack. If the fiber content is too low, it cannot adequately adhere to the polyester siloxane organic particles to provide sufficient overlap. Therefore, by controlling the mass ratio of biomass nanofibers to polyester siloxane organic particles in the coating within the above range, the tensile and puncture resistance of the separator can be improved, thereby enhancing the safety and reliability of the battery cells.

[0013] In some feasible implementations, the total mass percentage F of polyester siloxane organic particles and biomass nanofibers, based on the total mass of the organic coating, satisfies: 10% ≤ F ≤ 50%. Optionally, the total mass percentage F of polyester siloxane organic particles and biomass nanofibers, based on the total mass of the organic coating, satisfies: 20% ≤ F ≤ 30%. If the content of the mixture of polyester siloxane organic particles and biomass nanofibers in the organic coating is too high, it will affect the air permeability of the separator; conversely, if the content is too low, it will not enhance the tensile and puncture resistance of the separator. Therefore, by controlling the content of the mixture of polyester siloxane organic particles and biomass nanofibers within the above range, it is possible to improve the tensile and puncture resistance of the separator while maintaining its air permeability, thereby improving the safety and reliability of the battery cells.

[0014] In a second aspect, a battery is provided, comprising a battery cell as described in the first aspect and any possible implementation thereof.

[0015] Thirdly, an electrical device is provided, comprising the battery of the second aspect and any possible implementation thereof. Attached Figure Description

[0016] To more clearly illustrate the technical solutions of the embodiments of this application, the drawings used in the embodiments of this application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on the drawings without creative effort.

[0017] Figure 1 This is a scanning electron microscope image of an organic coating according to an embodiment of this application;

[0018] Figure 2 This is a schematic diagram of a battery cell according to an embodiment of this application;

[0019] Figure 3 This is a schematic diagram of the structure of a battery cell according to an embodiment of this application;

[0020] Figure 4 This is a schematic diagram of a battery according to an embodiment of this application;

[0021] Figure 5 This is a schematic diagram of an electrical device according to an embodiment of this application;

[0022] Figure 6 This is a schematic diagram of another electrical device according to an embodiment of this application.

[0023] Reference numerals: 1: Battery cell; 31: Housing; 32: End cap assembly; 33: Electrode assembly; 34: Connecting member; 322: Electrode terminal; 331: Tab; 5: Battery; 6: Automobile; 7: Energy storage device. Detailed Implementation

[0024] Embodiments of the battery cell, battery, and power-consuming device of this application have been described in detail with appropriate reference to the accompanying drawings; however, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of practically identical structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided to enable those skilled in the art to fully understand this application and are not intended to limit the subject matter of the claims.

[0025] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values ​​of 1 and 2 are listed, and if maximum range values ​​of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0026] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.

[0027] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.

[0028] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.

[0029] The development of battery technology requires consideration of various design factors, such as energy density, cycle life, capacity, and safety and reliability. The separator base film in a battery cell is typically PE or PP film, which, while possessing excellent chemical stability and electrical insulation, has relatively weak tensile and puncture strength, limiting its application, especially in high-energy-density and high-safety batteries. When the separator film is wound and stretched, or when the cell is punctured, it can rupture, causing a short circuit between the positive and negative electrodes and reducing the safety and reliability of the battery cell.

[0030] In existing related technical solutions, a combination of inorganic and organic materials is commonly used as a coating method. For example, alumina, boehmite, and polyacrylic acid are applied to the base membrane. The inorganic material itself has a certain mechanical strength, while the organic material acts as a binder, increasing the adhesion between the inorganic material and the base membrane. This can improve the tensile strength and puncture strength of the separator to some extent. However, the above method does not significantly improve the tensile strength and puncture strength of the separator. Furthermore, the inorganic particles in such inorganic coatings are usually dot-like reinforcements, and the fracture between coating particles easily forms microcracks, resulting in high brittleness. This makes them prone to cracking during bending or winding, and even in higher-end batteries, the separator's mechanical properties remain insufficient.

[0031] Therefore, improving battery separators to enhance the safety and reliability of individual battery cells is a pressing technical problem. In view of this, this application provides a battery cell comprising: a separator, the separator including a base film and an organic coating, the organic coating being located on at least one side surface of the base film, the organic coating comprising polyester siloxane organic particles and biomass nanofibers, wherein the biomass nanofibers coat at least a portion of the surface of the polyester siloxane organic particles.

[0032] In this embodiment, an organic coating is introduced on at least one side of the base membrane of the separator. The coating uses polyester-based siloxane organic particles as the main filler, which has good flexibility and thermal stability, and can improve the shrinkage resistance of the separator. At the same time, biomass nanofibers are introduced into the coating, which combine with the polyester-based siloxane organic particles and coat at least part of the surface of the polyester-based siloxane organic particles. Since the surface of the biomass nanofibers contains many oxygen-containing groups, strong hydrogen bonds can be formed between the fibers, resulting in very high strength and modulus of the biomass nanofibers. The polyester-based siloxane organic particles also have a large specific surface area, and the surface of the particles also has polar groups such as hydroxyl groups that form strong hydrogen bonds with the biomass nanofibers, providing conditions for the adhesion of biomass nanofibers. By coating the polyester-based siloxane organic particles with biomass nanofibers, the slippage between the polyester-based siloxane organic particles can be suppressed while ensuring the separator has shrinkage resistance, thereby improving the overall flexibility of the organic coating, and thus improving the tensile properties and puncture resistance of the separator, and improving the safety and reliability of the battery cell.

[0033] The aforementioned organic coating is applied to at least one side of the base membrane of the separator. It is a functional surface coating composed primarily of polyester-based siloxane organic particles encapsulated in biomass nanofibers, supplemented with a polymer binder. This coating enhances the tensile strength, puncture strength, and thermal stability of the separator. The morphology of the polyester-based siloxane organic particles in the coating includes microspheres.

[0034] In the embodiments of this application, a single battery cell can refer to the smallest structural unit of a battery. Multiple battery cells can first be assembled into a battery module, and then the battery module can be assembled into a battery (battery pack); multiple battery cells can also be directly assembled into a battery.

[0035] [Battery cell]

[0036] like Figure 1 The image shown is a scanning electron microscope (SEM) image of an organic coating according to an embodiment of this application.

[0037] This application provides a battery cell, including: a separator, the separator including a base film and an organic coating, the organic coating being located on at least one side surface of the base film, the organic coating including polyester siloxane organic particles and biomass nanofibers, wherein the biomass nanofibers coat at least a portion of the surface of the polyester siloxane organic particles.

[0038] In this embodiment, an organic coating is introduced onto the base film surface of the separator. This coating uses polyester-based siloxane organic particles as the main filler, exhibiting good flexibility and thermal stability, which enhances the separator's anti-shrinkage ability. Simultaneously, biomass nanofibers are introduced into the coating, combining with the polyester-based siloxane organic particles and coating at least a portion of their surface. Because the biomass nanofibers contain many oxygen-containing groups, strong hydrogen bonds can form between the fibers, resulting in very high strength and modulus. The polyester-based siloxane organic particles also have a large specific surface area, and their surface contains polar groups such as hydroxyl groups that form strong hydrogen bonds with the biomass nanofibers, providing conditions for their adhesion. Coating the biomass nanofibers onto the polyester-based siloxane organic particles improves the separator's tensile and puncture resistance while maintaining its anti-shrinkage properties, thereby enhancing the safety and reliability of the battery cell.

[0039] In some embodiments, the aspect ratio D of the biomass nanofibers in the above-mentioned organic coating satisfies: 20:3 ≤ D ≤ 100:1. Specifically, D can be 20:3, 8:1, 10:1, 20:1, 30:1, 40:1, 50:1, 60:1, 70:1, 80:1, 90:1, 100:1, or a value within the range obtained by any combination of the above two values. If the aspect ratio of the biomass nanofibers is too large, their specific surface area will be larger, which will cause agglomeration between the biomass nanofiber materials. If the aspect ratio is too small, their specific surface area will be smaller, which will result in less overlap between the biomass nanofiber materials, making it difficult to effectively transfer external forces and achieve a significant reinforcing effect. Therefore, by controlling the aspect ratio of the biomass nanofibers within the above range, the biomass nanofibers can have better mechanical properties in the separator, improving the tensile and puncture resistance of the separator and enhancing the safety and reliability of the battery cells.

[0040] In some embodiments, the length of the biomass nanofibers in the organic coating is between 100 nm and 500 nm. Specifically, the length of the biomass nanofibers can be 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, or 500 nm, or a value within the range obtained by any combination of the above two values. If the biomass nanofibers are too long, they cannot effectively coat the surface of the organic particles; if they are too short, the overlap between the biomass nanofibers will be insignificant, failing to effectively transfer external forces and thus failing to provide a significant reinforcing effect. Therefore, by controlling the length of the biomass nanofibers within the above range, the biomass nanofibers in the separator can have better mechanical properties, improving the tensile and puncture resistance of the separator and enhancing the safety and reliability of the battery cells.

[0041] In some feasible implementations, the diameter of the biomass nanofibers in the organic coating meets the requirement of 5nm to 15nm. Specifically, the diameter of the biomass nanofibers can be 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, 11nm, 12nm, 13nm, 14nm, or 15nm, or a value within the range obtained by any combination of the above two values. If the diameter of the biomass nanofibers is too large, it will reduce the specific surface area of ​​the biomass nanofibers, resulting in insignificant interlocking between the biomass nanofiber materials, making it difficult to effectively transfer external forces and failing to achieve a significant reinforcing effect. If the diameter of the biomass nanofibers is too small, the mechanical properties will not meet the requirements, and the reinforcing effect will also be ineffective. Therefore, by controlling the diameter of the biomass nanofibers within the above range, the biomass nanofibers in the separator can have better mechanical properties, improve the tensile and puncture resistance of the separator, and enhance the safety and reliability of the battery cells.

[0042] In some embodiments, the specific surface area A of the above-mentioned polyester siloxane organic particles satisfies: 10 m² / g. 2 / g≤A≤100m 2 / g. Specifically, A can be 10m 2 / g, 15m 2 / g、20m 2 / g、25m 2 / g、30m 2 / g、35m 2 / g、40m 2 / g、45m 2 / g, 50m 2 / g、60m 2 / g、65m 2 / g、70m 2 / g、75m 2 / g、80m 2 / g、90m 2 / g, 100m 2 / g, or a value within the range obtained by any combination of the above two values. By controlling the specific surface area of ​​the polyester siloxane organic particles within this range, biomass nanofibers can better adhere to and coat the particle surface, allowing for better bonding between the two. If the specific surface area of ​​the polyester siloxane organic particles is too large, agglomeration will occur between the particles; if the specific surface area is too small, there will not be enough surface area for the biomass nanofibers to adhere, causing the nanofibers to remain in a free state within the coating. Therefore, by controlling the specific surface area of ​​the polyester siloxane organic particles within this range, the tensile and puncture resistance of the separator can be improved, thereby enhancing the safety and reliability of the battery cells.

[0043] In some embodiments, the mass ratio E of biomass nanofibers to polyester siloxane organic particles in the organic coating of the separator membrane satisfies: 1:99 ≤ E ≤ 1:9. Specifically, E can be 1:99, 1:90, 1:85, 1:80, 1:75, 1:70, 1:65, 1:60, 1:55, 1:50, 1:45, 1:40, 1:30, 1:25, 1:20, 1:15, 1:9, or a value within the range obtained by any combination of the above two values. Biomass nanofibers in the coating serve as reinforcing fillers. If the fiber content is too high, the biomass nanofibers will adhere excessively in the mixture of biomass nanofibers and polyester siloxane organic particles, existing in an agglomerated form. Since biomass nanofibers are high-modulus and high-strength materials, their agglomerated state makes the entire coating hard and brittle, resulting in poor film formation and easy cracking. Conversely, if the fiber content is too low, it cannot adequately adhere to and overlap between the polyester siloxane organic particles. Therefore, by controlling the mass ratio of biomass nanofibers to polyester siloxane organic particles in the coating within the aforementioned range, the tensile and puncture resistance of the separator can be improved, thereby enhancing the safety and reliability of the battery cells.

[0044] In some embodiments, based on the total mass of the organic coating, the total mass percentage F of polyester siloxane organic particles and biomass nanofibers satisfies: 10% ≤ F ≤ 50%. Specifically, F can be 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, or a value within the range obtained by any combination of the above two values. Optionally, based on the total mass of the organic coating, the total mass percentage F of polyester siloxane organic particles and biomass nanofibers satisfies: 20% ≤ F ≤ 30%. Specifically, F can be 20%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, or a value within the range obtained by any combination of the above two values. If the content of the mixture of polyester siloxane organic particles and biomass nanofibers in the organic coating is too high, it will affect the air permeability of the separator. Conversely, if the content is too low, it will not enhance the tensile and puncture resistance of the separator. Therefore, by controlling the content of the mixture of polyester siloxane organic particles and biomass nanofibers within the aforementioned range, it is possible to improve the tensile and puncture resistance of the separator while maintaining its air permeability, thereby enhancing the safety and reliability of the battery cells.

[0045] In some feasible methods, the organic coating amount on one side of the separator membrane meets the following requirement: 0.01 g / m³. 2 -10g / m 2 Specifically, the organic coating application rate can be 0.01 g / m². 2 0.1g / m2 0.5g / m 2 1g / m 2 1.5g / m 2 2g / m 2 2.5g / m 2 3g / m 2 3.5g / m 2 4g / m 2 4.5g / m 2 5g / m 2 5.5g / m 2 6g / m 2 6.5g / m 2 7g / m 2 7.5g / m 2 8g / m 2 8.5g / m 2 9g / m 2 9.5g / m 2 10g / m 2 The value, or its value, must fall within the range obtained by combining any two of the above values. Excessive coating amount on one side of the separator will affect its air permeability, while insufficient coating amount will fail to provide better mechanical properties. Therefore, by controlling the coating amount within the above range, it is possible to improve the tensile and puncture resistance of the separator while maintaining its air permeability, thereby enhancing the safety and reliability of the battery cells.

[0046] In some feasible implementations, the thickness of the organic coating on one side of the separator meets the requirement of 1μm-10μm. Specifically, the organic coating thickness can be 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, 5.5μm, 6μm, 6.5μm, 7μm, 7.5μm, 8μm, 8.5μm, 9μm, 9.5μm, 10μm, or a value within the range obtained by any combination of the above two values. If the organic coating on one side of the separator is too thick, it will affect the separator's air permeability; if the coating is too thin, it will not provide the separator with better mechanical properties. Therefore, by controlling the coating thickness within the above range, the tensile properties and puncture resistance of the separator can be improved while maintaining its air permeability, thereby improving the safety and reliability of the battery cells.

[0047] This application does not impose any particular limitation on the shape of the battery cell; it can be cylindrical, square, or any other arbitrary shape. For example, Figure 2 This is a battery cell 1 as an example. It should be understood that battery cell 2 may include the battery cell in the foregoing embodiments.

[0048] Figure 3This is a schematic diagram of the structure of a battery cell 1 according to an embodiment of this application. For example, as shown... Figure 3 As shown, the battery cell 1 is a square battery cell. The battery cell 1 includes a housing 31, an end cap assembly 32, and an electrode assembly 33 disposed in the housing 31.

[0049] The electrode assembly 33 can be made from a positive electrode, a negative electrode, and a separator through a winding process or a stacking process.

[0050] End cap assembly 32 includes electrode terminals 322, such as Figure 3 As shown, the end cap assembly 32 includes two electrode terminals 322, one of which is a positive electrode terminal and the other is a negative electrode terminal.

[0051] The battery cell 1 also includes a connecting member 34, which is used to connect the tabs 331 and the electrode terminals 322 of the electrode assembly 33.

[0052] In some embodiments, individual battery cells can be assembled into a battery module. The number of individual battery cells contained in a battery module can be one or more, and the specific number can be selected by those skilled in the art based on the application and capacity of the battery module.

[0053] [Positive electrode plate]

[0054] The positive electrode includes a positive current collector and a positive film layer disposed on at least one surface of the positive current collector.

[0055] The positive electrode current collector can be a metal foil or a composite current collector. For example, the positive electrode current collector can be an aluminum foil.

[0056] Composite current collectors may include a polymeric material substrate and a metal layer formed on at least one surface of the polymeric material substrate. Composite current collectors can be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymeric material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0057] The positive electrode film layer includes a positive electrode active material. In some embodiments, the positive electrode active material may be a known positive electrode active material for batteries. As an example, the positive electrode active material may include at least one of the following materials: lithium phosphates with an olivine structure, lithium transition metal oxides, and their respective modified compounds. However, this application is not limited to these materials, and other conventional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides include, but are not limited to, lithium cobalt oxides (such as LiCoO2), lithium nickel oxides (such as LiNiO2), lithium manganese oxides (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxides, lithium manganese cobalt oxides, lithium nickel manganese oxides, and lithium nickel cobalt manganese oxides (such as LiNi). 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also known as NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2 (also known as NCM523), LiNi 0.5 Co 0.25 Mn 0.25 O2 (also known as NCM211), LiNi 0.6 Co 0.2 Mn 0.2 O2 (also known as NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2 (also known as NCM811), lithium nickel cobalt aluminum oxide (such as LiNi) 0.85 Co 0.15 Al 0.05 At least one of O2 and its modified compounds. Examples of lithium phosphates with an olivine structure include, but are not limited to, lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), lithium iron phosphate and carbon composites, lithium manganese phosphate (such as LiMnPO4), lithium manganese phosphate and carbon composites, lithium manganese iron phosphate, and lithium manganese iron phosphate and carbon composites.

[0058] The positive electrode film layer may optionally include a binder. As an example, the binder may include at least one selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resin.

[0059] The positive electrode film may optionally include a conductive agent. The conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0060] [Negative electrode plate]

[0061] One embodiment of this application provides a negative electrode sheet comprising a negative current collector and a layer of negative active material disposed on the negative current collector.

[0062] The negative electrode current collector can be a metal foil or a composite negative electrode current collector. The negative electrode current collector can be copper foil. Composite negative electrode current collectors can be formed by depositing metallic materials (copper, copper alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys, etc.) onto a polymer substrate (such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0063] The negative electrode film layer includes the negative electrode active material described in the above embodiments. The negative electrode active material can be any negative electrode active material known in the art for use in batteries. As an example, the negative electrode active material may include one or more of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate, etc. The silicon-based material may be selected from one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from one or more of elemental tin, tin oxide compounds, and tin alloys. However, this application is not limited to these materials, and other conventional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0064] The negative electrode active material layer may optionally include a binder. As an example, the binder may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), styrene-butadiene rubber, carboxymethyl cellulose, PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resins.

[0065] The negative electrode active material layer may optionally include a conductive agent. The conductive agent may be selected from one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0066] Electrolyte

[0067] The electrolyte acts as a conductor of ions between the positive and negative electrodes. This application does not impose specific limitations on the type of electrolyte; it can be selected according to requirements. For example, the electrolyte can be liquid, gel-like, or entirely solid.

[0068] In some embodiments, the electrolyte is an electrolyte solution. The electrolyte solution includes an electrolyte salt and a solvent.

[0069] Electrolyte salts may include one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorodioxalate phosphate, and lithium tetrafluorooxalate phosphate.

[0070] Solvents may include one or more of the following: ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butyl carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, methyl ethyl sulfone, and diethyl sulfone.

[0071] The electrolyte may also optionally include negative electrode film-forming additives, positive electrode film-forming additives, and performance additives that can improve certain battery performance, such as performance additives that improve battery overcharge performance, battery high temperature or low temperature performance, etc.

[0072] The electrolyte acts as a conductor of ions between the positive and negative electrodes. This application does not impose specific limitations on the type of electrolyte; it can be selected according to requirements. For example, the electrolyte can be liquid, gel-like, or entirely solid.

[0073] [Isolation Component]

[0074] The separator is used to separate the positive electrode and the negative electrode. This application does not impose any particular limitation on the type of separator; any known porous membrane with good chemical and mechanical stability can be selected.

[0075] The material of the separator can be selected from one or more of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film; there are no particular restrictions. When the separator is a multi-layer composite film, the materials of each layer can be the same or different; there are no particular restrictions.

[0076] The separator includes a base membrane and an organic coating. The organic coating is located on at least one side of the surface of the base membrane. The organic coating includes polyester siloxane organic particles and biomass nanofibers. The biomass nanofibers coat at least a portion of the surface of the polyester siloxane organic particles.

[0077] In some possible implementations, the aforementioned biomass nanofibers include at least one of cellulose nanofibers and chitin nanofibers.

[0078] In some possible implementations, the aforementioned polyester siloxane organic particles include at least one of: methylsiloxane stearate, aminopropylsiloxane-polyethylene glycol ester, and sulfonated siloxane-polyester copolymer.

[0079] Positive electrode, negative electrode and separator can be made into electrode assembly by winding process or stacking process.

[0080] [Battery]

[0081] This application provides a battery, including the battery cell described in the above embodiments. The battery cell can be a battery cell after formation and aging processes. Figure 4 This is a schematic diagram of a battery according to an embodiment of this application. Figure 4 As shown, battery 5 may include multiple battery cells (not shown in the figure).

[0082] Battery cells can be directly assembled into battery 5, or they can be first assembled into battery modules, and then multiple battery modules can be assembled into battery 5.

[0083] [Electrical appliances]

[0084] This application provides an electrical device, including the battery described in the above embodiments.

[0085] In some embodiments, the electrical device includes an energy storage device or a truck. Energy storage devices and trucks have high requirements for the lifespan and long-term cycle performance of individual battery cells. Applying individual battery cells to the aforementioned electrical devices can improve the lifespan of the electrical devices.

[0086] Electrical devices can also be lighting devices, spacecraft, etc., and the embodiments of this application include, but are not limited to, these.

[0087] Figure 5 This is a schematic diagram of an electrical device according to an embodiment of this application. Figure 5 As shown, this application provides an electrical device for a vehicle 6. As one example, the battery in the vehicle 6 can be swapped using a battery swapping device to replace a low-charge battery with a fully charged one. As another example, the battery in the vehicle 6 can be charged using a charging device (e.g., a charging station).

[0088] Figure 6 This is a schematic diagram of an electrical device according to an embodiment of this application. Figure 6 As shown, this application provides an electrical device, which is an energy storage device 7, and the energy storage device 7 may include multiple batteries 5. The energy storage device 7 can be applied to a power storage station to store and release electrical energy.

[0089] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.

[0090] [Example]

[0091] Example 1

[0092] [Preparation of battery cells]

[0093] (1) Preparation of the positive electrode sheet:

[0094] The positive electrode active material lithium iron phosphate, the lithium supplement agent dilithium dicarboxylic acid hydrazine, the conductive agent carbon black, and the binder polyvinylidene fluoride (PVDF) are mixed evenly in a weight ratio of 92:3:2:3. The mixture is then stirred evenly again, and a certain amount of N-methylpyrrolidone solvent is added. The positive electrode slurry is obtained under the action of a vacuum stirrer. The positive electrode slurry is evenly coated onto aluminum foil. After the aluminum foil is dried at room temperature, it is transferred to a 120°C oven to dry for 4 hours. Then, it is cold-pressed and cut to obtain the positive electrode sheet.

[0095] (2) Preparation of negative electrode sheet:

[0096] The negative electrode active material hard carbon, conductive agent carbon black, binder styrene-butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) were dissolved in deionized water at a weight ratio of 95.2:1.8:1.8:1.2 and a negative electrode slurry was obtained under vacuum stirring. The negative electrode slurry was uniformly coated onto copper foil. After the copper foil was dried at room temperature, it was transferred to a 120°C oven to dry for 4 hours. Then, it was cold-pressed and slit to obtain the negative electrode sheet.

[0097] (3) Preparation of the separating membrane:

[0098] Cellulose nanofibers coated with methylsiloxane stearate organic particles: 1% cellulose nanofiber gel was added to a dispersion of 28% methylsiloxane stearate organic particles and mechanically stirred for 4 hours to prepare a mixed suspension of the two. The suspension was then spray-dried to obtain a powder of cellulose nanofibers coated with methylsiloxane stearate organic particles, wherein the mass percentage of cellulose nanofibers in the powder of cellulose nanofibers coated with methylsiloxane stearate organic particles was 1%.

[0099] An organic coating slurry was prepared by mixing the powder of cellulose nanofibers coated with methylsiloxane stearate organic particles, a binder (polyacrylic acid), and water in a mass ratio of 7:6.48:49.27. The prepared organic coating slurry was then coated onto at least one surface of a porous polyethylene film, with a coating weight of 2 g / m². 2 The organic coating thickness is 9μm.

[0100] (4) Preparation of electrolyte:

[0101] An electrolyte was prepared by mixing 13 wt% lithium hexafluorophosphate, 33 wt% ethylene carbonate, 28 wt% dimethyl carbonate, 24 wt% methyl ethyl carbonate, and 2 wt% ethylene sulfate.

[0102] (5) Preparation of lithium-ion batteries:

[0103] The positive electrode, separator, and negative electrode are wound and placed in the order of "separator-negative electrode-separator-positive electrode" and assembled together with other battery components to obtain a wound battery cell.

[0104] Examples 2-6

[0105] The difference between Examples 2-4 and Example 1 is that the proportion of biomass nanofibers in polyester siloxane organic particles and biomass nanofibers is different.

[0106] Examples 5-7

[0107] The difference between Examples 5-7 and Example 1 is that the specific surface area of ​​the polyester siloxane organic particles is different.

[0108] Example 8

[0109] The difference between Example 8 and Example 1 is that the biomass nanofibers have different lengths and different aspect ratios.

[0110] Example 9

[0111] The difference between Example 9 and Example 1 is that the types of polyester siloxane organic particles and the types of coatings are different.

[0112] Example 10

[0113] The difference between Example 9 and Example 1 is that the proportions of polyester siloxane organic particles and biomass nanofibers in the coating are different.

[0114] Comparative Example 1

[0115] The difference between Comparative Example 1 and Example 1 is that there is no coating.

[0116] Comparative Example 2

[0117] The difference between Comparative Example 2 and Example 1 is that the coating types, coating amounts, and coating thicknesses are different.

[0118] The battery cells of Examples 2-9 and Comparative Examples 1-2 are prepared using methods similar to those of the battery cell of Example 1, but the composition and product parameters of the separator coating are adjusted. The different product parameters are detailed in Table 1.

[0119] Table 1. Specific parameters of Examples 1-10 and Comparative Examples 1-2

[0120]

[0121]

[0122]

[0123] [Tensile Strength Test]

[0124] Before testing, the sample is placed in an environment with a temperature of (23±2)℃ and a relative humidity of (50±5)% for at least 24 hours to ensure the consistency of the testing conditions. In the specific implementation process, an electronic universal testing machine can be used as the tensile testing device. The testing machine is equipped with corresponding clamps, which can ensure the stable clamping of the sample during the test and avoid test errors caused by slippage or torsion.

[0125] The test used type 2 specimens with a width of (15±0.1) mm, an initial gauge length between the fixtures of (100±5) mm, and a tensile speed of (250±10) mm / min.

[0126] During the test, the force-displacement data of the specimens are recorded. No less than 5 parallel specimens are tested for each group of samples. The final result is the average value, and then the maximum tensile strength of the diaphragm material is calculated.

[0127] [Puncture Strength Test]

[0128] Lay the diaphragm flat in the fixture and clamp it. Puncture the diaphragm at a rate of (100±10) mm / min. After puncturing, remove the sample and, according to GB / T6672-2001, test the thickness at four points around the film. Take the average value and calculate the thickness using the formula:

[0129]

[0130] Calculate the puncture intensity, where F p The puncture intensity is expressed in Newtons per micrometer (N / μm); F0 is the force measured when the diaphragm is punctured, expressed in Newtons (N). This represents the average thickness of the diaphragm, expressed in micrometers (μm).

[0131] [Puncture pressure drop test]

[0132] Using a high-temperature resistant steel needle with a diameter of 1 mm, insert it into the geometric center of the battery cell from a direction perpendicular to the battery plates at a speed of 0.01 mm / s. During the puncture, measure the voltage between the positive electrode and the steel needle (hereinafter referred to as "positive-to-needle voltage"). When the positive-to-needle voltage > 1V, hold the steel needle in that position for 5 seconds, and then continue to insert it for 0.13 mm at the same speed (0.01 mm / s) to obtain a stable positive-to-needle voltage (nV). Stop and do not withdraw the needle (the stop can be set to 600 seconds) to monitor the voltage drop stability. Subsequently, continue to insert the steel needle at a speed of 0.01 mm / s until the total insertion depth reaches 1.5 mm. At this point, stop moving and keep the needle tip in a fixed position for 1.5 hours (90 minutes) to further observe the voltage change characteristics of the battery cell under continuous local stress and contact conditions.

[0133] The batteries of each embodiment were prepared according to the above method, and the performance parameters were measured. The results are shown in Table 2 below.

[0134] Table 2 Test results of Examples 1-10 and Comparative Examples 1-2

[0135]

[0136]

[0137] In conjunction with Example 1 and Comparative Examples 1-2,

[0138] In Comparative Example 1, no coating was applied to the surface of the diaphragm base membrane. At this time, the tensile strength of the diaphragm was 100 MPa, the puncture strength was 0.25 N / μm, and the voltage drop after 1.5 h was 120 mV, with drastic voltage changes.

[0139] In Comparative Example 2, the surface of the diaphragm base membrane was coated with a conventional CCS coating. Compared with Comparative Example 1, the tensile strength of the diaphragm increased to 153 MPa, the puncture strength increased to 0.33 N / μm, and the voltage drop after 1.5 h became 110 mV, indicating that the voltage change was still relatively drastic.

[0140] In Example 1, the surface of the diaphragm base membrane is provided with an organic coating comprising cellulose nanofibers encapsulating methylsiloxane stearate organic particle microspheres, the organic particles having a specific surface area of ​​10 m². 2 / g, the proportion of cellulose nanofibers in the mixture formed by the two is 1%, the proportion of the mixture in the organic coating is 10%, the length of cellulose nanofibers is 500nm, the aspect ratio of cellulose nanofibers is 100:1. Compared with Comparative Example 1 and Comparative Example 2, the tensile strength of the diaphragm increases to 181MPa, the puncture strength increases to 0.42N / μm, the voltage drop at 1.5h decreases to 86mV, and the voltage change at 1.5h is relatively gradual.

[0141] In conjunction with Examples 1-4 and Comparative Examples 1-2,

[0142] In Comparative Example 1, no coating was applied to the surface of the diaphragm base membrane. At this time, the tensile strength of the diaphragm was 100 MPa, the puncture strength was 0.25 N / μm, and the voltage drop after 1.5 h was 120 mV, with drastic voltage changes.

[0143] In Comparative Example 2, the surface of the diaphragm base membrane was coated with a conventional CCS coating. Compared with Comparative Example 1, the tensile strength of the diaphragm increased to 153 MPa, the puncture strength increased to 0.33 N / μm, and the voltage drop after 1.5 h became 110 mV, indicating that the voltage change was still relatively drastic.

[0144] In Example 1, the surface of the diaphragm base membrane is provided with an organic coating comprising cellulose nanofibers encapsulating methylsiloxane stearate organic particle microspheres, the organic particles having a specific surface area of ​​10 m². 2 / g, the proportion of cellulose nanofibers in the mixture formed by the two is 1%, the proportion of the mixture in the organic coating is 10%, the length of cellulose nanofibers is 500nm, the aspect ratio of cellulose nanofibers is 100:1. Compared with Comparative Example 1 and Comparative Example 2, the tensile strength of the diaphragm increases to 181MPa, the puncture strength increases to 0.42N / μm, the voltage drop at 1.5h decreases to 86mV, and the voltage change at 1.5h is relatively gradual.

[0145] In Examples 2-4, the surface of the diaphragm base membrane is coated with an organic coating consisting of cellulose nanofibers encapsulating methylsiloxane stearate microspheres. Compared to Example 1, the specific surface area of ​​the organic particles in Examples 2-4 is 10 m². 2The proportions of cellulose nanofibers in the mixture formed by the two components were 3%, 5%, and 10%, respectively, while the proportion of the mixture in the organic coating was 10% for all components. The length of the cellulose nanofibers was 500 nm, and the aspect ratio of the cellulose nanofibers was 100:1 for all components. As the fiber proportion gradually increased, the tensile strength of the diaphragm increased to 197 MPa, 211 MPa, and 235 MPa, respectively, and the puncture strength increased to 0.49 N / μm, 0.54 N / μm, and 0.57 N / μm, respectively. The voltage drop after 1.5 h decreased to 79 mV, 71 mV, and 64 mV, respectively, showing a relatively gradual voltage change. Compared with Comparative Examples 1 and 2, the tensile strength and puncture strength of the diaphragm were improved, and the voltage change after 1.5 h was relatively gradual.

[0146] In conjunction with Examples 1, 5-7, and Comparative Examples 1-2,

[0147] In Comparative Example 1, no coating was applied to the surface of the diaphragm base membrane. At this time, the tensile strength of the diaphragm was 100 MPa, the puncture strength was 0.25 N / μm, and the voltage drop after 1.5 h was 120 mV, with drastic voltage changes.

[0148] In Comparative Example 2, the surface of the diaphragm base membrane was coated with a conventional CCS coating. Compared with Comparative Example 1, the tensile strength of the diaphragm increased to 153 MPa, the puncture strength increased to 0.33 N / μm, and the voltage drop after 1.5 h became 110 mV, indicating that the voltage change was still relatively drastic.

[0149] In Example 1, the surface of the diaphragm base membrane is provided with an organic coating comprising cellulose nanofibers encapsulating methylsiloxane stearate organic particle microspheres, the organic particles having a specific surface area of ​​10 m². 2 / g, the proportion of cellulose nanofibers in the mixture formed by the two is 1%, the proportion of the mixture in the organic coating is 10%, the length of cellulose nanofibers is 500nm, the aspect ratio of cellulose nanofibers is 100:1. Compared with Comparative Example 1 and Comparative Example 2, the tensile strength of the diaphragm increases to 181MPa, the puncture strength increases to 0.42N / μm, the voltage drop at 1.5h decreases to 86mV, and the voltage change at 1.5h is relatively gradual.

[0150] In Examples 5-7, the surface of the diaphragm base membrane is coated with an organic coating consisting of cellulose nanofibers encapsulating methylsiloxane stearate microspheres. Compared to Example 1, the specific surface area of ​​the organic particles in Examples 2-4 is 40 m². 2 / g、70m 2 / g, 100m 2The proportion of cellulose nanofibers in the mixture formed by both was 1% in both samples, and the proportion of the mixture in the organic coating was 10% in both samples. The length of the cellulose nanofibers was 500 nm in both samples, and the aspect ratio of the cellulose nanofibers was 100:1 in both samples. As the specific surface area of ​​the organic particles gradually increased, the tensile strength of the diaphragm increased to 188 MPa, 193 MPa, and 198 MPa, respectively, and the puncture strength increased to 0.45 N / μm, 0.48 N / μm, and 0.51 N / μm, respectively. The voltage drop at 1.5 h was 87 mV, 88 mV, and 89 mV, respectively, and the voltage change was relatively gradual. Compared with Comparative Example 1 and Comparative Example 2, the tensile strength and puncture strength of the diaphragm were improved, and the voltage change at 1.5 h was relatively gradual.

[0151] In conjunction with Examples 1, 8-10, and Comparative Examples 1-2,

[0152] In Comparative Example 1, no coating was applied to the surface of the diaphragm base membrane. At this time, the tensile strength of the diaphragm was 100 MPa, the puncture strength was 0.25 N / μm, and the voltage drop after 1.5 h was 120 mV, with drastic voltage changes.

[0153] In Comparative Example 2, the surface of the diaphragm base membrane was coated with a conventional CCS coating. Compared with Comparative Example 1, the tensile strength of the diaphragm increased to 153 MPa, the puncture strength increased to 0.33 N / μm, and the voltage drop after 1.5 h became 110 mV, indicating that the voltage change was still relatively drastic.

[0154] In Example 1, the surface of the diaphragm base membrane is provided with an organic coating comprising cellulose nanofibers encapsulating methylsiloxane stearate organic particle microspheres, the organic particles having a specific surface area of ​​10 m². 2 / g, the proportion of cellulose nanofibers in the mixture formed by the two is 1%, the proportion of the mixture in the organic coating is 10%, the length of cellulose nanofibers is 500nm, the aspect ratio of cellulose nanofibers is 100:1. Compared with Comparative Example 1 and Comparative Example 2, the tensile strength of the diaphragm increases to 181MPa, the puncture strength increases to 0.42N / μm, the voltage drop at 1.5h decreases to 86mV, and the voltage change at 1.5h is relatively gradual.

[0155] In Example 8, the surface of the diaphragm base membrane is provided with an organic coating comprising cellulose nanofibers encapsulating methylsiloxane stearate microspheres. Compared to Example 1, the specific surface area of ​​the organic particles in Example 8 remains unchanged at 10 m². 2 / g, the proportion of cellulose nanofibers in the mixture formed by the two is 1%, the proportion of the mixture in the organic coating is 10%, the length of the cellulose nanofibers is changed to 100nm, the aspect ratio of the cellulose nanofibers is changed to 5:1. As the aspect ratio of the cellulose nanofibers decreases, the tensile strength of the diaphragm decreases to 155MPa, the puncture strength decreases to 0.35N / μm, and the voltage drop at 1.5h is 88mV. Compared with Comparative Example 1 and Comparative Example 2, the tensile strength and puncture strength of the diaphragm are improved, and the voltage change at 1.5h is relatively gradual.

[0156] In Example 9, the surface of the diaphragm base membrane is provided with an organic coating comprising cellulose nanofibers encapsulating aminopropylsiloxane-polyethylene glycol microspheres. Compared to Example 1, the specific surface area of ​​the organic particles in Example 9 remains unchanged at 10 m². 2 / g, the proportion of cellulose nanofibers in the mixture formed by the two is 1%, the proportion of the mixture in the organic coating is 10%, the length of the cellulose nanofibers is 500nm, and the aspect ratio of the cellulose nanofibers remains unchanged at 100:1. With the change of organic particle type, the tensile strength of the diaphragm decreases to 168MPa, the puncture strength decreases to 0.35N / μm, and the voltage drop at 1.5h is 90mV. Compared with Comparative Example 1 and Comparative Example 2, the tensile strength and puncture strength of the diaphragm are improved, and the voltage change at 1.5h is relatively gradual.

[0157] In Example 10, the surface of the diaphragm base membrane is provided with an organic coating comprising cellulose nanofibers encapsulating methylsiloxane stearate microspheres. Compared to Example 1, the specific surface area of ​​the organic particles in Example 10 remains unchanged at 10 m². 2 The cellulose nanofibers comprised 1% of the mixture, while their proportion in the organic coating increased to 50%. The length of the cellulose nanofibers was 500 nm, and their aspect ratio remained constant at 100:1. As the proportion of the mixture in the organic coating increased, the tensile strength of the diaphragm increased to 185 MPa, the puncture strength increased to 0.51 N / μm, and the voltage drop over 1.5 h was 88 mV. Compared to Comparative Examples 1 and 2, both the tensile strength and puncture strength of the diaphragm were improved, and the voltage change over 1.5 h was relatively gradual.

[0158] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.

Claims

1. A battery cell, characterized in that, include: The separator membrane includes a base membrane and an organic coating; The organic coating is located on at least one side surface of the base film; The organic coating comprises polyester siloxane organic particles and biomass nanofibers, wherein the biomass nanofibers coat at least a portion of the surface of the polyester siloxane organic particles.

2. The battery cell according to claim 1, characterized in that, The aspect ratio D of the biomass nanofibers satisfies: 20:3≤D≤100:

1.

3. The battery cell according to claim 1 or 2, characterized in that, The length of the biomass nanofibers is 100nm to 500nm.

4. The battery cell according to any one of claims 1 to 3, characterized in that, The biomass nanofibers include at least one of cellulose nanofibers and chitin nanofibers.

5. The battery cell according to any one of claims 1 to 4, characterized in that, The polyester-based siloxane organic particles include at least one of the following: methylsiloxane stearate, aminopropylsiloxane-polyethylene glycol ester, and sulfonated siloxane-polyester copolymer.

6. The battery cell according to any one of claims 1 to 5, characterized in that, The specific surface area A of the polyester-based siloxane organic particles satisfies: 10m² 2 / g≤A≤100m 2 / g.

7. The battery cell according to any one of claims 1 to 6, characterized in that, In the organic coating, the mass ratio E of the biomass nanofibers to the polyester siloxane organic particles satisfies: 1:99≤E≤1:

9.

8. The battery cell according to any one of claims 1 to 7, characterized in that, Based on the total mass of the organic coating, the total mass ratio F of the polyester siloxane organic particles and the biomass nanofibers satisfies: 10% ≤ F ≤ 50%.

9. The battery cell according to any one of claims 1 to 8, characterized in that, Based on the total mass of the organic coating, the total mass ratio F of the polyester siloxane organic particles and the biomass nanofibers satisfies: 20% ≤ F ≤ 30%.

10. A battery, characterized in that, Includes the battery cell as described in any one of claims 1 to 9.

11. An electrical appliance, characterized in that, Includes the battery as described in claim 10.